Antibacterial Potential Test of Cream Preparation of Ethanol Extract of Matoa Stem Bark (Pometia pinnata) against Staphylococcus aureus. - Violeta Gavelentri Melga Tambingon; Paulina Yamlean; Jainer Siampa (PHARMACON, 2023)
Skin diseases can be caused by several factors, one of which is a bacterial infection. One of the bacteria that causes infection is Staphylococcus aureus. The results of previous studies showed that the ethanolic extract of the bark of matoa (Pometia pinnata) had antibacterial potential. This study aims to test the quality of cream preparations including homogeneity test, organoleptic test, pH test, adhesion test and dispersibility test, as well as to test the antibacterial activity of cream preparations ethanol extract of matoa stem bark. The matoa bark extract was obtained by maceration method using 95% ethanol as solvent. The antibacterial activity test was carried out using the well method, with a concentration variation of 0.5%, 1.5%, 2.5% and 3.5%. The test results showed that all the parameters of the test preparation, namely homogeneity test, organoleptic test, pH test, adhesion test and spreadability test met the requirements of the quality of the preparation. Antibacterial testing showed cream preparations with a concentration of 3.5% produced the largest inhibition zone of 8.66 mm which was included in the category of moderate inhibition.